VITAMIN D PADA PASIEN ACNE VULGARIS DAN KORELASI DENGAN LUARAN KLINIS: REVIEW SISTEMATIK - Pratama, Radya Putra; Arjadi, Fitranto; Mulyanto, Joko (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Background: Vitamin D is thought to have a role in the pathogenesis of acne vulgaris through anti-inflammatory effects. Research regarding the relationship between vitamin D and the severity of acne vulgaris still shows mixed results. Objective: To determine the correlation between vitamin D levels and clinical severity in acne vulgaris patients. Method: This systematic review uses Pubmed, Google Scholar, and Science Direct databases. Of the 362 articles, 13 articles that met the inclusion criteria were analyzed narratively. Results: Of 13 studies, 4 showed significant differences in serum vitamin D levels between degrees of acne severity. Meanwhile, the other 9 did not show any significant differences. One study showed significant differences in tissue vitamin D levels with severity. Conclusion: Overall, results are still inconsistent. There is evidence of a higher risk of vitamin D deficiency and decreased tissue vitamin D levels in people with acne vulgaris as severity increases. It is suspected that this is related to the role of vitamin D in suppressing inflammation. Further studies considering confounding factors are needed to clarify this association.